Juan Ansión: Professional trajectory and contributions to Peruvian anthropology - Ames, Patricia (2018)
This article addresses the professional trajectory of the Belgian-Peruvian anthropologist and sociologist Juan Ansión. His main research interests and his development over the years are presented, from his early work around mythical thinking in the Andean world to his sustained commitment to the issue of education in rural communities, expectations and projects on education and migration, and the impact of political violence in school. An issue that intersects the previous two - interculturality - arises from the need to conceptualize a new proposal that allows us to understand and challenge the relations of subordination and discrimination between cultures that Peruvian society experiences. Ansión will contribute significantly to the discussion around interculturality to this day, covering not only education, but also new fields, such as justice and health. The article addresses his role as a university professor, first at the National University of San Cristóbal de Huamanga - with which he maintained a close relationship over the years - and then at the Pontifical Catholic University of Peru, where he taught throughout more than three decades.